Case report of Barth syndrome: a forgotten cause of cardiomyopathy. Issue 7 (5th July 2021) - Rao, Shiavax; Kanwal, Arjun; Padmanabhan, Sriram
Abstract: Background: Barth syndrome (BTHS) is a rare X-linked recessive disorder characterized by clinical features including cardiomyopathy, skeletal myopathy, neutropenia, growth delay, and exercise intolerance. It is often considered to be a paediatric disease, owing to most cases being diagnosed during childhood and mortality being the highest during the first few years of life. Case summary: We report a case of dilated cardiomyopathy due to BTHS in a 27-year-old adult male patient, who initially presented with lightheadedness, dyspnoea, orthopnoea, and bilateral lower extremity oedema. Key findings from investigations included leukopenia, prolonged QTc interval, reduced left ventricular ejection fraction (LVEF), global enlargement of all heart chambers, patent coronary arteries, and mild pulmonary hypertension. The patient was diuresed to euvolemia and discharged with a LifeVest. Guideline-directed medical therapy was initiated and uptitrated as an outpatient. A repeat echocardiogram 2 years after initial presentation showed marked improvement in LVEF. Discussion: It is possible that there are adult patients with idiopathic cardiomyopathy, which may be attributable to BTHS. In the absence of an obvious underlying cause, with the appropriate historical information, clinical exam, laboratory investigations, and imaging findings, BTHS should be considered as a likely cause of non-ischaemic cardiomyopathy.